Case Report and Review: An Unusual Case of Fetal Traumatic Brain Injury - Kadariya, Ashraya; Rimal, Pragya Bharati; Poudel, Bikash Sharma; Bhagat, Chandra Shekhar; Khadka, Unnati; Acharya, Rupak (Medical Journal of Eastern Nepal, 2022)
We herein report an unusual case of maternal road traffic accident with blunt trauma to the abdomen at 34 weeks of gestation followed by delivery of severely encephalopathic baby and also a brief review of similar previous reports.The baby had near normal transition, then progressively developed severe encephalopathy and multiple organ dysfunction attributed mainly to the intrauterine traumatic injury. The baby had multiple intra and extra axial bleeds,cerebral edema and diffuse axonal injury, as revealed by the CT scan. The baby was managed conservatively with various neuroprotective strategies similar to management in older children and thus cerebral edema/ hematomas subsided. The baby required ventilatory support, prolonged assisted ventilation/oxygen and the metabolic derangements were managed accordingly. The baby was discharged on oral Levetiracetam, multivitamins and nasogastric tube feeds. Baby was followed up sequentially till day 74 and on physical examination had poor head growth and increased muscle tone of the extremities. Neuroimaging revealed diffuse multicystic leukoencephalomalacia, hydrocephalus ex vacuo with cortical thinning. Intrauterine fetal brain injury is an uncommon incidence which causes mortality and significant morbidity in the child. Neuroimaging of the fetus after trauma to the mother can lead to early diagnosis and anticipation. Early vigorous neuroprotective measures and management may prevent mortality and reduce further brain insult in theseneonates. There is paucity of information on management of such cases thus they should be reported in detail forstudy and future references.